Pengaruh Merokok terhadap Pembentukan Plak pada Gigi - Oriza Aditya; Eva Fauzia; Aldian Yusup (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2021)
Smoking is a bad habit that many people have, but this habit has a bad effect on health. One of the consequences of smoking is the formation of stains on the teeth. This study aims to determine the effect of smoking on the formation of stains on the teeth. This research is descriptive research, which aims to describe the condition of the respondents statistically. The research was conducted in November 2022. The research was carried out for one month by collecting respondent data from all puskesmas in Cirebon Regency, West Java. The research instruments used were interviews and checklists. The instrument records the age, length of smoking, shape of the cigarette and color of the respondent's teeth. Respondent criteria are active smokers from the age of 10 to 60 years and are willing to be research respondents. Respondents in this study numbered 112. The results showed that the color of the respondent's teeth were four colors, namely yellow, black, brown and dark brown. However, the most dominant tooth color was dark brown with a percentage of 55.4% or as many as 62 respondents out of 112 respondents. The conclusion of this study is that smoking can affect the formation of plaque on the teeth. Plaque formation on the teeth is most commonly found with dark brown teeth.